Praktik Perubahan Biodata Kutipan Akta Nikah ditinjau Menurut PMA 20 Tahun 2019 - Aulia Az-Zahra Kirani (Jurnal Riset Hukum Keluarga Islam, 2023)
Abstract. Marriage registration aims to provide legal certainty for husband, wife, and children. Registration of marriage is evidenced by a marriage book. However, in the implementation of marriage registration, it is not uncommon for writing errors to occur in the marriage certificate quotation biodata which can hinder other state administration arrangements. PMA Number 20 of 2019 concerning Marriage Registration has regulated the procedure for changing the marriage book biodata in Article 37 to be carried out by the Head of the KUA. However, what happened at the Astanaanyar District Office of Religious Affairs, several changes to the marriage book biodata were made by KUA staff. This study aims to find out the practice of changing marriage book biodata at the Astanaanyar District Office of Religious Affairs in connection with PMA Number 20 of 2019 concerning Marriage Registration. This study uses a case study approach and normative juridical. Primary data sources were obtained from laws and regulations and interview results, while secondary data sources were obtained from books, journals relevant. The results that the practice of changing the biodata of marriage books at the Astanaanyar District Office of Religious Affairs was generally in accordance with PMA Number 20 of 2019 concerning Marriage Registration, except regarding changes to the biodata of marriage books by the Head of KUA, this is not in accordance with practice, because there are still several changes made by KUA staff. Abstrak. Pencatatan nikah bertujuan untuk memberikan kepastian hukum bagi suami, istri, maupun anak. Pencatatan nikah dibuktikan dengan kutipan akta nikah. Namun, dalam pelaksanaan pencatatan nikah tidak jarang terjadi kesalahan penulisan pada biodata kutipan akta nikah yang dapat menghambat dalam mengurus administrasi kenegaraan lainnya. PMA Nomor 20 Tahun 2019 tentang Pencatatan Pernikahan telah mengatur tentang prosedur perubahan biodata kutipan akta nikah pada Pasal 37 harus dilakukan oleh Kepala KUA. Namun yang terjadi di KUA Kecamatan Astanaanyar, beberapa perubahan biodata kutipan akta nikah dilakukan oleh Staf KUA. Penelitian ini bertujuan untuk mengetahui praktik perubahan biodata kutipan akta nikah di KUA Kecamatan Astanaanyar dihubungkan dengan PMA Nomor 20 Tahun 2019 tentang Pencatatan Pernikahan. Penelitian ini menggunakan pendekatan studi kasus dan yuridis normatif. Sumber data primer diperoleh dari peraturan perundang-undangan dan hasil wawancara, sedangkan sumber data sekunder diperoleh dari buku, jurnal yang relevan. Hasil penelitiannya bahwa praktik perubahan biodata kutipan akta di KUA Kecamatan Astanaanyar pada umumnya sudah sesuai dengan PMA Nomor 20 Tahun 2019 tentang Pencatatan Pernikahan, kecuali mengenai perubahan biodata kutipan akta nikah oleh Kepala KUA, hal ini tidak sesuai dengan praktiknya, karena masih terdapat beberapa perubahan yang dilakukan oleh Staf KUA.